Attitudes toward Organizational Change Strategies among Healthcare Professionals and Administrative Staff: An Applied Study in King Fahd Medical City, Riyadh - Mana Alshahrani; Mohammed Alshamrani; Sami Mohamed Alhabib (The Saudi Journal of Health Systems Research)
Introduction: This study aimed to examine employee attitudes toward organizational change (OC) and various management strategies, and to explore the relationship of these attitudes with demographic and professional factors. Additionally, the study analyzed the factors of resistance to OC. Methods: A cross-sectional study was conducted among 323 staff members at King Fahd Medical City, Riyadh, Saudi Arabia, during September 2022. The questionnaire collected demographic and professional data and explored attitudes toward OC (eight items) and four specific management strategies including re-educative (six items), persuasion (six items), facilitation (six items), and power-coercive (six items). The model hypothesizes that attitudes toward OC are determined by attitudes toward the various management strategies as well as by demographic and professional factors. Results: We observed a broad acceptance of OC along with a strong favorability for re-educative strategy, followed by persuasive and facilitation strategies. However, the power-coercive strategy was less accepted. There were significant differences in attitudes based on demographic and professional factors, notably nationality and job category. Independent factors associated with resistance to OC included employee nationality (non-Saudi: OR = 2.65; 95% CI: 1.17–5.96), job category (health technicians: OR = 0.21; 95% CI: 0.07–0.62), and favorable attitudes toward power-coercive (OR = 0.04; 95% CI: 0.01–0.13) and facilitation strategies (OR = 0.23; 95% CI: 0.08–0.61). The model explained 31.3% to 42.1% of the variance in resistance to OC. Conclusion: To enhance acceptance of OC in healthcare, leadership should prioritize re-educative strategies, integrate persuasive and power-coercive elements where appropriate, and adopt flexible, hybrid approaches tailored to demographic and professional differences. Transparent communication, employee engagement, and diversity-sensitive policies are essential for effective change implementation.